Evidence for high gene flow, nonrandom mating, and genetic bottlenecks of Ganoderma boninense infecting oil palm (Elaeis guineensis Jacq.) plantations in Malaysia and Indonesia. (2nd November 2022) - Wong, W. C.; Tung, H. J.; Nurul Fadhilah, M.; Midot, F.; Lau, S. Y. L.; Melling, L.; Astari, S.; Hadziabdic, Đ.; Trigiano, R. N.; Goh, Y. K.; Goh, K. J.
ABSTRACT: Ganoderma boninense, the causal agent of basal stem rot (BSR) disease, has been recognized as a major economic threat to commercial plantings of oil palm ( Elaeis guineensis Jacq.) in Southeast Asia, which supplies 86% of the world's palm oil. High genetic diversity and gene flow among regional populations of 417  G. boninense isolates collected from Sabah, Sarawak, and Peninsular Malaysia (Malaysia) and Sumatra (Indonesia) were demonstrated using 16 microsatellite loci. Three genetic clusters and different admixed populations of G. boninense across regions were detected, and they appeared to follow the spread of the fungus from the oldest (Peninsular Malaysia and Sumatra) to younger generations of oil palm plantings (Sabah and Sarawak). Low spatial genetic differentiation of G. boninense (FST  = 0.05) among the sampling regions revealed geographically nonrestricted gene dispersal, but isolation by distance was still evident. Analysis of molecular variance (AMOVA) confirmed the little to no genetic differentiation among the pathogen populations and the three genetic clusters defined by STRUCTURE and minimum spanning network. Despite G. boninense being highly outcrossing and spread by sexual spores, linkage disequilibrium was detected in 7 of the 14 populations. Linkage disequilibrium indicated that the reproduction of the fungus was not entirely by random mating and genetic drift could be an important structuring factor. Furthermore, evidence of population bottleneck was indicated in the oldest oil palm plantations as detected in genetic clusters 2 and 3, which consisted mainly of Peninsular Malaysia and Sumatra isolates. The population bottleneck or founding event could have arisen from either new planting or replanting after the removal of large number of palm hosts. The present study also demonstrated that migration and nonrandom mating of G. boninense could be important for survival and adaptation to new palm hosts.